Structural Microfoundations of Innovation - Grigoriou, Konstantinos; Rothaermel, Frank T. (Journal of Management, 2014)
Conceptualizing new knowledge development as a process of search and recombination, we suggest that a focus on individual productivity alone presents an undersocialized view of human capital. Rather, we emphasize the importance of embedded relationships by individuals to effectively perform knowledge-generating activities. We rely on intraorganizational knowledge networks emerging through individual collaboration to identify actors who can positively influence their organization’s knowledge outcomes. We study two types of such relational stars: integrators (outliers in centrality) and connectors (outliers in bridging behavior). We test our ideas using the patenting portfolios of 106 pharmaceutical firms from 1974 to 1998 predicting the effect of relational stars on their firm’s quantity and quality of inventive output—proxies for the firm’s capacity to develop more and better new knowledge stocks. We find that the presence of relational stars results in firm-level knowledge advantages not only through their own superior recombinant efforts, but also through their capacity to make others around them more effective at knowledge recombination. Relational stars are firm-specific, and their advantages are socially complex and causally ambiguous because they rely on a network of within-firm interactions. Relational stars, therefore, are prime candidates to be a source of sustainable firm-level knowledge advantage.